Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the MK2 Inhibitor ATI-450 in Healthy Subjects: A Placebo-Controlled, Randomized Phase 1 Study - Gordon D; Hellriegel ET; Hope HR; Burt D; Monahan JB (Dove Medical Press, 2021)
David Gordon,1 Edward T Hellriegel,1 Heidi Rath Hope,2 David Burt,1 Joseph B Monahan2 1Research and Development, Aclaris Therapeutics, Inc., Wayne, PA, USA; 2Research and Development, Aclaris Therapeutics, Inc., and Confluence Discovery Technologies, Inc., St. Louis, MO, USACorrespondence: David GordonChief Medical Officer, Research and Development, Aclaris Therapeutics, Inc., 640 Lee Road, Suite 200, Wayne, PA, 19087, USATel +1 484-540-6273Email dgordon@aclaristx.comPurpose: ATI-450 is an oral, small-molecule inhibitor of the p38α mitogen-activated protein kinase (MAPK)/MAPK-activated protein kinase 2 (MK2) inflammatory signaling pathway. This phase 1, single and multiple ascending dose (SAD, MAD) study evaluated ATI-450 safety, tolerability, pharmacokinetics, and pharmacodynamics.Patients and Methods: Healthy adults were randomly assigned to SAD (10, 30, 50, 100 mg; n=24) and MAD (10, 30, 50 mg twice daily [BID] for 7 days; n=24) cohorts of ATI-450 or placebo (n=14). Safety and tolerability were evaluated through clinical and laboratory assessments. Pharmacokinetic parameters were evaluated in plasma samples; pharmacodynamic assessments included quantification of cytokine levels (tumor necrosis factor α [TNF-α], interleukin [IL]-1β, IL-6, IL-8) and phosphorylation of the MK2 downstream substrate, heat shock protein 27 (p-HSP27).Results: The most common adverse events were headache (10/48, 20.8%), dizziness (6/48, 12.5%), upper respiratory tract infection (3/48, 6.3%), and constipation (3/48, 6.3%). Pharmacokinetics were dose-proportional, with a terminal half-life of 9‒12 hours in the MAD cohorts on day 7. Dose- and concentration-dependent inhibition of ex vivo stimulated cytokines and target biomarker was observed. On day 7, patients in the 50 mg BID dose cohort recorded mean trough drug levels that were 1.4, 2.2, 2.3, and 2.4 times greater than the IC80 for TNF-α, IL-1β, IL-8, and p-HSP27, respectively. Mean Cmax was 3.5, 5.4, 5.6, and 6.0 times greater than the IC80 for TNF-α, IL-1β, IL-8, and p-HSP27, respectively. IL-6 inhibition > 50% was noted for part of the dosing interval.Conclusion: ATI-450 was well tolerated at the doses investigated, exhibited dose- and time-independent (ie, linear) pharmacokinetics, and dose-related pharmacodynamic effects. These results support further study of ATI-450 in immunoinflammatory diseases in phase 2 trials.Keywords: immunologic diseases, rheumatoid arthritis, serine-threonine kinases, protein kinase inhibitors, pharmacokinetics/pharmacodynamics